2008
DOI: 10.1007/s10086-007-0909-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of density profile of MDF on stiffness and strength of nailed joints

Abstract: Nail-head pull-through, lateral nail resistance, and single shear nailed joint tests were conducted on medium density fiberboard (MDF) with different density profiles, and the relations between the results of these tests and the density profiles of MDF were investigated. The maximum load of nail-head pull-through and the maximum load of nailed joints were little affected by the density profile. However, the ultimate strength of lateral nail resistance, the stiffness, and the yield strength of nailed joints wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The profile over the different zones of the thickness resembled a symmetric “m‐shape,” with peak densities appearing near the board top and bottom surfaces (zones 1 and 3), and the lowest density in the core region (zone 2). Similar observations of higher surface and lower core density using commercial adhesives are extensively reported in the literature . The presence of this vertical density gradient is known to result in higher bending strength, but lower internal bond strength .…”
Section: Resultssupporting
confidence: 85%
“…The profile over the different zones of the thickness resembled a symmetric “m‐shape,” with peak densities appearing near the board top and bottom surfaces (zones 1 and 3), and the lowest density in the core region (zone 2). Similar observations of higher surface and lower core density using commercial adhesives are extensively reported in the literature . The presence of this vertical density gradient is known to result in higher bending strength, but lower internal bond strength .…”
Section: Resultssupporting
confidence: 85%
“…Vertical density profile of ROSB panels prepared with CPA adhesives also showed similar density variations as compared to typical composite panels, where it showed a symmetric "M" shape with a higher density in two surfaces of the panels, and a low density in the panel core. 42,43 The presence of density profile is beneficial in improving the bending strength (MOE) of the composite panel. However, a very low density core has a detrimental effect on the internal bond strength of OSB panels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was considered that the shear strength of structural PB was high because of higher density of structural PB. It was reported that the properties of nail joint shear were proportional to density of members (Smith et al 2001;Sawata et al 2008;Sandhaas and Görlacher 2018). Therefore, the entire shear strength of wall might increase because the shear property of the nail joint used in structural PB will be high.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the shear modulus of structural PB light-frame shear wall was lower than that of OSB light-frame shear wall. There was a positive relationship between the density of the wood-based material's surface layer and the nail joint's stiffness (Sawata et al 2008). Therefore, additional research might be needed to increase the shear modulus of structural PB walls considering the stiffness of the nail joint.…”
Section: Resultsmentioning
confidence: 99%